Observational Constraints on Models with an Interaction between Dark Energy and Dark Matter - Costa, André Alencar da (2014)
In this thesis we go beyond the standard cosmological LCDM model and study the effect of an interaction between dark matter and dark energy. Although the LCDM model provides good agreement with observations, it faces severe challenges from a theoretical point of view. In order to solve such problems, we first consider an alternative model where both dark matter and dark energy are described by fluids with a phenomenological interaction given by a combination of their energy densities. In addition to this model, we propose a more realistic one based on a Lagrangian density with a Yukawa-type interaction. To constrain the cosmological parameters we use recent cosmological data, the CMB measurements made by the Planck satellite, as well as BAO, SNIa, H0 and Lookback time measurements.